Endoscopic treatment of nonstricture-related benign biliary diseases using covered self-expandable metal stents - Irani, Shayan; Baron, Todd H.; Law, Ryan; Akbar, Ali; Ross, Andrew S.; Gluck, Michael; Gan, Ian; Kozarek, Richard A. (Endoscopy, 2015)
Background and study aims: Nonstricture benign biliary diseases (BBDs) such as leaks, perforations, and bleeding, have been traditionally managed by placement of one or more plastic stents. Emerging data support the use of covered, self-expandable, metal stents (CSEMSs). The aim of this study was to assess the outcomes of endoscopic temporary placement of CSEMS in patients with nonstricture BBD.Patients and methods: This was a retrospective study of CSEMS placement for BBD between May 2005 and August 2013 at two tertiary care centers. The main outcome measures were resolution of perforation, bleeding, leak, and adverse events related to CSEMS treatment.Results: A total of 87 patients were included (median age 62 years [range 18 – 86]). Indications for stent placement were bile leaks (n = 35, 40 %), bleeding (n = 27, 31 %), perforation (n = 18, 21 %), and other conditions (n = 7, 8 %). Fully and partially covered 8 – 10-mm diameter CSEMS were placed and subsequently removed in all 87 patients (100 %). Resolution of the underlying problem was achieved for 33 bile leaks (94 %), 25 bleedings (93 %), 18 perforations (100 %), and for 3 cases with other indications (43 %). The median duration of stenting was 9 weeks in patients with biliary leaks, 3 weeks for bleeding, and 9.5 weeks for perforations. Median follow-up was 82 weeks after stent removal. Seven adverse events occurred, including cholangitis in six patients (7 %), and tissue hyperplasia leading to difficulty in the removal of a partially covered SEMS in one patient. Conclusions: Nonstricture BBD can be effectively and safely treated with the short term placement of CSEMS.